El déficit habitacional como un problema de economía social: el caso del Parque Indoamericano de Villa Soldati en Buenos Aires (Argentina) = The housing shortage as a problem of social economy : the case of the Parque Indoamericano of Villa Soldati, in Buenos Aires (Argentina) - García, Pablo Sebastián (Oñati Socio-Legal Series, 2012)
Herbert Simon formulated in 1979 a new approach to the theory of firm, which argued that economic rationality was not to be thought in the way that Milton Friedman did, i.e., in terms of utility maximization. This critical approach which Simon inaugurated has led to many critiques of mainstream economics. Besides the fundamental methodological criticism that can be formulated against Friedman’s perspective, the approach proposed by Simon involves a change of viewpoint. In fact, the theory of the firm, and of economic behaviour in general, is in Friedman and the “classical model” subordinated to market and price theory as the main object of economic analysis, but for Simon the actual behaviour of economic agents is the essential theme of that analysis. With this change in the way of understanding economic analysis many fundamental implications have been developed in many areas of economic research. In the present article the problem of the housing shortage in the city of Buenos Aires (Argentina) is examined, focusing on the occupation of a public space by homeless people. The argument is that the free capitalist market is incapable, because of its internal dynamics, of solving that kind of problem in emergent countries